2009
DOI: 10.1186/1756-3305-2-s1-s8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Rickettsia felis in dog and cat fleas (Ctenocephalides felis) from Italy

Abstract: : Rickettsia felis is an obligate intracellular bacterium belonging to the spotted fever group, suspected to cause a murine typhus-like illness in humans, with a cosmopolitan distribution. This study was designed to estimate presence and occurrence of this pathogen in fleas collected from dogs and cats in different areas of Italy. Two species of fleas were identified, Ctenocephalides felis (80.3%) and Ctenocephalides canis (19.7%).Overall, 320 fleas (257 C. felis and 63 C. canis) collected from 117 animals (73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 20 publications
(24 reference statements)
3
22
1
2
Order By: Relevance
“…This study also recorded a higher percentage in fleas from cats (17.6%) than in fleas from dogs (10.2%) [25].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This study also recorded a higher percentage in fleas from cats (17.6%) than in fleas from dogs (10.2%) [25].…”
Section: Discussionsupporting
confidence: 58%
“…In our previous research carried out on fleas collected from foxes in the same area, we observed no positivity in 32 C. canis and in other 76 fleas of various species, while the only two C. felis were both positive [27]. Other authors have reported the absence [25],[41],[42] or a low prevalence [39],[40] in larger sample sizes, in contrast to what has been observed in France, where 27.03% of C. canis (10/37) were infected [37].…”
Section: Discussionmentioning
confidence: 60%
“…R. felis has been associated with fleas worldwide, in Algeria and Morocco (37), Italy (38), and the United States (39). However, in this investigation, the prevalence of R. felis (1%) is lower than that reported in Morocco (20% in C. felis fleas removed from sheep, cats, and dogs [37]) and in Italy (11.9% in dog and cat fleas [38]). …”
Section: Discussioncontrasting
confidence: 53%
“…Ctenocephalides felis is the most common flea species infesting dogs and cats in Italy followed by Ctenocephalides canis [5,26]. Recent investigations have revealed the occurrence of Rickettsia felis DNA in C .…”
Section: Arthropod Vectors and Related Pathogens Affecting Dogs And Cmentioning
confidence: 99%